GE_GERICHTE P/20195/2021 vom 5. November 2024 - GE Cour de justice (2024)
DISPOSITIONS PÉNALES DE LA LEI;FAUX MATÉRIEL DANS LES TITRES;CONDITION DE RECEVABILITÉ | LEI.118; LEI.115; CP.251; CPP.399.al3